Analysis of glycemic index of "Gula Semut" through blood glucose level test. (May 2019) - Winarni, S; Arifan, F; Broto, RTD. W; Fuadi, A; Ramadhan, R
Abstract: The glycemic index is a measure developed to classify carbohydrate foods based on their physiological effects on blood glucose levels. The purpose of this study was to distinguish glycemic index of ant sugar compared to comparator (carbohydrate 50 gram). Respondents involved in the glycemic index test were 5 persons. Prior to treatment (fresh bread and "gula semut") respondents fasting at least 10 hours. In the first stage respondents were given 50 grams of fresh bread measured blood sugar levels at 0 minutes (fasting), 15, 30, 45, 60, 90, and 120 minutes post giving bread. Respondents were rested for 3 days without heavy activity. The second stage of the respondents was given 50 grams of ant sugar and measured blood sugar level of 0 minutes (fasting), 15, 30, 45, 60, 90, and 120 minutes post giving "Gula semut". Blood glucose measurement using finger-prick capillary blood samples method. Calculation of glycemic index to bread and "gula semut" obtained through calculation of area under the curve. The total area under the curve on the supply of bread 35.75% while the total area under the curve on the supply of "gula semut" 14.10%. The glycemic index of "gula semut" is low (<55%). Low glycemic index foods improve slowly blood sugar levels. So the "gula semut" does not raise the blood glucose levels quickly.